Tumor‐specific and photothermal‐augmented chemodynamic therapy by ferrocene‐carbon dot‐crosslinked nanoparticles. Issue 2 (21st May 2022) - Sun, Shan; Chen, Qiao; Li, Yike; Yu, Yao; Li, Zhongjun; Lin, Hengwei
Abstract: Extensive research have been devoted to the exploration of multifunctional theranostic agents for cancer, but the poor tumor specificity and unsatisfactory treatment efficacy are some of the critical obstacles for their clinical translations. Herein, ferrocene‐carbon dot‐crosslinked nanoparticles (Fc‐CD NPs) were designed and fabricated for achieving highly specific and photothermal‐augmented chemodynamic therapy (CDT). The Fc‐CD NPs were found not only to inherit the immanent fluorescence, photoacoustic, and photothermal properties of carbon dots (CDs), but also be endowed with CDT that could occur selectively in tumor microenvironment (TME) due to the presence of Fc for triggering Fenton reaction. Moreover, the enlarged particle size of Fc‐CD NPs facilitated their effective accumulation at tumor sites, thus realizing great improvement for antitumor treatment outcomes. Once docking at tumor and being exposed to 660 nm laser irradiation, significantly amplified CDT effect of Fc‐CD NPs was observed due to heat‐accelerating generation of reactive oxygen species (ROS). More interestingly, since the produced ROS could in turn alleviate the thermal‐resistance of photothermal therapy (PTT), the therapeutic efficiency of integrated PTT and CDT was synergized to the maximum extent. This study on the one hand provides a facile approach to fabricate CDs‐based multifunctional theranostic nanoplatform with enhanced tumor accumulation and specificity, on the other hand emphasizes the merits of synergizing mutually beneficial therapeutic modalities for more efficient cancer therapy. Abstract : A tumor‐specific and photothermal‐augmented chemodynamic therapy (CDT) is developed based on ferrocene‐carbon dot‐crosslinked nanoparticles (Fc‐CD NPs), which highlights the merits of mutually beneficial therapeutic modalities (photothermal therapy [PTT] and CDT) and provides a promising paradigm for more effective and safer cancer theranostic.